THE LATIN AMERICAN UNIVERSITY PROFESSOR: TOWARDS AN ETHICAL, SCIENTIFIC AND SOCIAL RESPOSIBILITY - Soto Arango, Diana Elvira (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2011)
The topic of “ ethical- Scientific- social responsibility”  of a university  professor in Latin America is introduced from the question  whether the Latin America university  has trained and is actually training its teaching faculty  with  professional capacity to lead the educational and cultural transformation, the social, technological and scientific changes, all of them seen from ethics, solidarity, tolerance, and inclusion  in the ever-changing “knowledge societies” of the 21th century. Both mission and vision of the 21th centuryLatin Americauniversity are  co-related to the university professor’s profile.